Novel small 99mTc-labeled affibody molecular probe for PD-L1 receptor imaging - Liang, Zhigang; Hu, Xianwen; Hu, Hongyu; Wang, Pan; Cai, Jiong (Frontiers in Oncology, 2022)
Objective: In vivo imaging of programmed death ligand 1 (PD-L1) can monitor changes in PD-L1 expression and target PD-1/PD-L1 therapy. A 99mTc-labeled affibody molecular probe targeting PD-L1 receptor was prepared and evaluated its tracing effect in PD-L1-overexpressing colon cancer. Methods: PD-L1 affibody was prepared by genetic recombineering. The 99mTc labeling of the affibody was achieved by sodium glucoheptonate and SnCl2 labeling system. The labeling rate, radiochemical purity, stability in vitro were determined by instant thin layer chromatography (ITLC), MC38-B7H1 (PD-L1 positive) and MC38 (PD-L1 negtive) colon cancer cells was used to evaluate its affinity to PD-L1 by cell binding experiments. The biodistribution of the 99mTc-labeled affibody molecular probe was then determined in C57BL/6J mice bearing MC38-B7H1 tumors, and tumor targeting was assessed in C57BL/6J mice with MC38-B7H1, MC38 double xenografts. Result: The maximum nondecayed corrected yield of the 99mTc-PD-L1 affibody molecular probe was 95.95%, and showed good stability both in phosphate buffered saline (PBS) and fetal bovine serum (FBS) within 6 h. The affinity of the 99mTc-PD-L1 affibody molecular probe for cell binding assays was 10.02 nmol/L. Single photon emission computed tomography (SPECT) imaging showed rapid uptake of tracer in PD-L1-positive tumors, while very little tracer retention in PD-L1-negative control tumors. The tracer was significantly retained in the kidneys and bladder, suggesting that it is mainly excreted through the urinary system. Heart, liver, lung and muscle tissue showed no significant radioactive retention. The biodistribution in vitro also showed significant renal retention, a small amount of uptake in the thyroid and gastrointestinal tract, rapid blood clearance, and the tumor-to-blood radioactivity uptake ratio peaked 120 minutes after drug injection. Conclusion: The 99mTc-PD-L1 affibody molecular probe that we prepared can effectively target to PD-L1-positive tumors imaging in vivo, and clear in blood quickly, no obvious toxic side effects, which is expected to become a new type of tracer for detecting PD-L1 expression in tumors.